Vibro–acoustic assessment of vehicle body structures and trim materials. (4th August 2014) - Olatunbosun, O.A.; Cheng, K.W.
The technique of using structural dynamic performance parameters, based on mechanical mobility, for assessing the acceptability of vehicle Body–in–White structures, from a vibro–acoustic point of view, was first introduced in the late 1970s and has been successfully applied in the design and development of a number of new vehicle models. A steady improvement in the dynamic performance of vehicle structures has been reflected in better refinement of cars, particularly at the luxury end of the market. The high levels of refinement achieved by some recently introduced models have resulted in a revision of previous working standards. Along with these standards, the technique has been extended to establish the vibro–acoustic performance of the structure in terms of conversion of the input vibrational energy into acoustic energy radiated into the vehicle interior at various stages of trim. This technique can be used to quantify the effectiveness of trim material applied to the vehicle body structure.